Pengaruh penguasaan penggunaan Mikroskop Binokuler terhadap nilai praktikum MATEKLAB - Sulistiyawati Sulistiyawati; Sutriyono Sutriyono (Integrated Lab Journal, 2016)
This study aims to determine whether there is influence between mastery of the use of a dissecting microscope to the value of laboratory techniques in management practicum student of biology education courses 2015 academic year 2015/2016. This research is a quantitative research, the independent variable is the mastery of the use of a binocular microscope, while the value of the dependent is a practical value. Collecting data using the method of documentation and testing methods such as pre-test and post test. To know domination influence of binoculer microscope to value practicum at this research applies correlation analysis and one way anova. From one way anova analysis can be concluded that the 5% significance level there is a real effect between mastery binocular microscope to count the value of his lab where F = 3,292 with significant value 0.046. From inferential one way anova analysis that with level of signifikasi 5% there is real influence between dominations of binocular microscope to value practicum where F calculate is = 3.292 with value signifikasi 0,046